Reversed Student Mobility: Canadian Exchange Students’ Motivations for Studying in Mainland China - Yu, Shuai (Journal of International Students, 2023)
In order to promote Canadian students’ mobility to China, it is essential to understand their motivations to study in Chinese universities because it influences their learning experiences. Applying the push-pull model (Altbach, 1998; Mazzarol & Soutar, 2002), this study explores the factors that motivate Canadian exchange students to study in China. Semi-structured interviews were conducted with 14 non-Chinese spoken Canadian exchange students from 9 universities. The findings reveal that both push and pull factors affect students’ decisions to study in China. The key push factor is learning the Chinese language and culture and personal growth; the primary pull factors are China’s potential for economic development and future opportunities and the availability of programs. This study provides stakeholders insight into designing exchange programs targeted to students’ needs and developing marketing strategies to attract Canadian international students.